PENGARUH KOMPETENSI PROFESIONAL DAN KECERDASAN EMOSIONAL TERHADAP KINERJA GURU DIMODERASI SUPERVISI AKADEMIK KEPALA SEKOLAH DI SMP NEGERI SEKECAMATAN TAMAN - BANDIYANTO, 1352 02 0086; Fauzan, Muhamad (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to determine how the influenc of Professional Competence and Emotional Intelligence of Teacher Performance moderated Academic Supervision of Principal population heads in this research is all public secondary school teacher PNS distric of Taman. Collecting data by distributing questionnaires to be filled by responden. Test for normality distributed residual value normal. Heteroscedasticity test three main variables Heteroskedastisitas not happen because the significance value > 0,05. Hypotheses accepted that Professional Competence, Emotional Intelligence, and Academic Supervision Positive and Significant impact on Teacher PerformanceKeywords : Professional Competence, Emotional Intelligence, Academic Supervision, Teacher Performance.